Uzbekistan Economic Report, April 2013 : Economic Development and Reforms - Achievements and Challenges - World Bank (World Bank, Washington, DC, 2017)
This regular economic report records the economic activities of Uzbekistan for the year 2013-2014. Uzbekistan’s outlook remains largely dependent on commodity prices. The chief external factors affecting economic performance of Uzbekistan are favorable global commodity price trends for gold, gas, cotton, and copper. Although remittance inflows may suffer as the outlook weakens for Russia, government increases in wages and social payments will help to sustain private consumption. Thus, growth in Uzbekistan is not expected to slow down considerably, as surplus current account, high fiscal savings, external reserves, ongoing investment program and wage increase and remittance inflow in 2013–14 would mitigate the impacts of a continued global slowdown. However, the poor business environment will continue to deter most Western investors, and the authorities likely to continue impeding private-sector activity by retaining currency controls and high tariffs and excise taxes on imports. Inflation is expected to remain at around 7 percent in 2013–15. Global food prices are forecast to gradually decline, and more modest growth in net foreign assets and monetary indicators would offset higher government spending and limit inflationary pressure. Although the short-term growth outlook remains favorable, downside risks are high due to a still weak global situation. The first risk is external and stems from a possible slowdown in economic activity in Russia (and a consequent reduction in remittance flows to Uzbekistan) and likely lower prices for some of Uzbekistan’s traditional commodity exports. The second risk is internal and comes from inappropriate integration of generally sound macroeconomic policies with weak structural policies in the country that negatively affect business incentives and hamper improvements in productivity and appropriate job creation making long term growth unsustainable.